Praktik Pencegahan dan Penanganan Stunting Melalui Pendampingan Pada Kegiatan Posyandu di Jember Kidul, Kabupaten Jember - Shafira, Firyal Eka Putri; Kusbianto, Dwi Erwin; Cahya, Dita Wulan; Khasanah, Himmatul (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Stunting is a condition in which a child experiences failure to thrive due to lack of nutritional intake received from the womb. Generally, stunting sufferers are only seen when they are 2 years old. Indonesia has a high number of stunting sufferers and the government continues to strive to reduce this number. Jember Regency is one of the cities that has a high rate of stunting and IMR rates. This happens because there are still many people who lack knowledge about stunting and the importance of balanced nutrition, especially for toddlers at 1000 HPK. Apart from lack of knowledge, the cause of stunting can also be due to errors in parenting or there are financial problems in the family. The purpose of this activity is to provide basic knowledge about stunting and its prevention as well as provide knowledge about the intake of nutritious food to reduce the number of stunting sufferers. The method used is the action research method, where this activity begins with observation first and then continues by conducting socialization and giving a few gifts for the intended target. The expected result of this activity is that the targets can understand the importance of balanced nutritional intake for toddlers, especially during 1000 HPK and be able to correct errors in their parenting patterns to avoid stunting.